The secret gospel of Mark a poet's memoir - Reece, Spencer 1963- (New York, NY Seven Stories Press, 2020)
O love, how did you get here? -- Why should you be one too? -- A broken altar -- To be brought down -- Keep fast hold of your parents -- But where I say hours I mean years -- Follow me.
"The Secret Gospel of Mark is a powerful dynamo of a story that delicately weaves the author's experiences with an appreciation for seven great literary touchstones: Elizabeth Bishop, Sylvia Plath, Emily Dickinson, James Merrill, Mark Strand, George Herbert, and Gerard Manley Hopkins. In speaking to the beauty these poets' works inspire in him, Reece finds the beauty of his own life's journey, a path that runs from coming of age as a gay teenager in the 1980s, Yale, alcoholism, a long stint as a Brooks Brothers salesman, Harvard Divinity School, and leads finally to hard-won success as a poet, reconciliation with his family, and the fulfillment of finding his life's work as an Episcopal priest. Reece's writing approaches the truth and beauty of the writers who have influenced him; elliptical and direct, always beautifully rendered"--
Keywords: Reece, Spencer; Poets, American -- Biography; Gay clergy -- United States -- Biography; Poetry -- History and criticism